Tantangan Dosen dalam Mengaplikasikan Transformasi Nilai Ikhlas di STAIN Tgk. Dirundeng Meulaboh - Syahminan Syahminan; Mulia Rahman (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
State Islamic College (STAIN) Tgk. Dirundeng Meulaboh- West Aceh, is one of the tertiary institutions in Aceh which plays a very strategic role in creating a generation of intellectual and spiritual intelligence, so it requires lecturers who are able to transfer knowledge and values (morals) appropriately. One of the campus challenges is how to make the lacturers truly have sincerity in themselves and be able to be applied in their daily life while teaching. This study uses descriptive qualitative analysis methods, data collection techniques are observation, interviews, and documentation. The determination of research objects at STAIN Tgk. Dirundeng Meulaboh was invited because the campus is very strategically located in the west-south coast of Aceh, and is able to bring students from all over Aceh to study at the campus. The Results of the study: the understanding of lecturers and students regarding the transformation of sincere values is more in being able to carry out learning actually according to the SOP, and eliminating interference with the implementation of learning. The challenge of transforming the sincere value is the commitment of the lecturer himself in carrying out the mandate as a lecturer who is a religious professional (sincere)